Volost administration in the Statute on Siberian provincial administration of 1822 (To the 250th birth anniversary of Michael Speransky) - I. A. Konovalov (Правоприменение)
The subject. Many shortcomings in the current state of local government and self-government systems are that in the process of forming the institutions of Russian public power, there were not evolutionary qualitative changes, but, on the contrary, there were processes of quantitative complication of mechanisms and institutions for the exercise of public power, making the role of the people in administrative processes impossible or insignificant.The experience of pre-revolutionary Siberian local self-government is a proven resource in historical practice for improving the organization of local government, as well as the mechanism of public administration, which was prepared on local, Siberian soil, and was not copied from the socio-political systems of foreign countries.The purpose of the article is to identify principles and features of the peasant self-government in Siberia laid down by the reform of the outstanding Russian statesman Michael Speransky.The theoretical and methodological basis of the research are the categories and principles of materialistic dialectics, formal-logical, systemic, comparative-legal and formal-legal methods.The main results. The conditions of life and traditions of self-governing peasant communities in Siberia made it possible for a very long period, up to the revolutionary upheavals of 1917, to find a solution that freed the crown government from the costs of the lower level of local government and its performance of the functions of administration and court in the Siberian village.Conclusions. Peasant self-government was endowed with state powers and included in the mechanism of state power according to the reform of Michael Speransky.